2021
DOI: 10.1021/jacs.1c04880
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Luminescent Nitrogen-Doped Nanographene as an Acid- and Metal-Sensitive Fluorophore for Optical Imaging

Abstract: Dibenzo­[hi,st]­ovalene (DBOV) has excellent photophysical properties, including strong fluorescence and high ambient stability. Moreover, the optical blinking properties of DBOV have enabled optical super-resolution single-molecule localization microscopy with an imaging resolution beyond the diffraction limit. Various organic and inorganic fluorescent probes have been developed for super-resolution imaging, but those sensitive to pH and/or metal ions have remained elusive. Here, we report a diaza-derivative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 91 publications
(136 reference statements)
0
41
0
Order By: Relevance
“…1i and Fig. S14 ) 30 . Structural characterizations indicated that there was a PAH structure in the CDs, which existed in the carbon core.…”
Section: Resultsmentioning
confidence: 98%
“…1i and Fig. S14 ) 30 . Structural characterizations indicated that there was a PAH structure in the CDs, which existed in the carbon core.…”
Section: Resultsmentioning
confidence: 98%
“…A striking demonstration of the wide applicability of heteroatom doped PAHs is provided by the synthesis of the diaza derivative of dibenzo[ hi,st ]ovalene (compound 33 , Scheme 7 ) [ 47 ]. Notably, in compound 33 , the two nitrogen atoms are located on the zig zag edges; nonetheless, compound 33 is stable as its all carbon parent compound [ 48 ].…”
Section: N-doped Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Furthermore, the insertion of heteroatoms into PAHs significantly improves their electronic properties without changing their frameworks [11] . Thus, heteroatom doping in such nonplanar PAHs is a key method to prepare a series of compounds for emergency applications [4d,12] …”
Section: Introductionmentioning
confidence: 99%